Dampak Pertumbuhan Penduduk terhadap Ketersediaan Lapangan Kerja di Kabupaten Tangerang - Ivanka Tri Agustin; Siti Nurbaiti; Akrom (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Rapid population growth in Tangerang Regency has created serious pressure on job availability. This study aims to analyze the impact of population growth on the labor market and formulate mitigation strategies. The method used is library research with content analysis of BPS data, relevant agency reports, and academic journals from the 2015–2025 period. Seven main findings of this study are: (1) population growth rate reaches 2.3% per year, dominated by migration; (2) the proportion of working-age population reaches 68%; (3) labor force growth (3.1%) far exceeds formal job growth (1.2%); (4) the informal sector covers 58% of workers with wages below the district minimum wage; (5) competency mismatch occurs with 25% of industrial vacancies unfilled; (6) the vocational training budget is only 0.7% of the regional budget; (7) employment absorption elasticity per investment has declined drastically. The study concludes that population growth without being balanced by formal job expansion and vocational education transformation will worsen hidden unemployment and structural poverty. Integrated strategies are needed, including population control, restructuring of vocational training centers, and labor-intensive investment incentives.